2014
DOI: 10.1051/parasite/2014025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of piroplasms in small ruminants in North-West Tunisia and the first genetic characterisation ofBabesia ovisin Africa

Abstract: In this study, the prevalence of piroplasms in sheep and goats was assessed with Giemsa-stained blood smear examination, PCR and nested PCR-restriction fragment length polymorphism (RFLP) to identify Babesia and Theileria species, respectively, in 338 small ruminants (172 sheep and 166 goats) from three sites in North-West Tunisia during the 2011 summer season. The overall infection prevalence of piroplasms in Giemsa-stained blood smears was 3.2% (11/338), with a parasitaemia ranging from 0.01 to 0.05%. PCR de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
29
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 32 publications
10
29
6
Order By: Relevance
“…This event matches with results reported by Rjeibi et al (2014) during an investigation on Babesia ovis in Tunisian sheep and goats.…”
Section: Discussionsupporting
confidence: 92%
“…This event matches with results reported by Rjeibi et al (2014) during an investigation on Babesia ovis in Tunisian sheep and goats.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, even if they are controlled, it is impossible to detect the presence of carrier‐state animals among a very long list of pathogens. In Tunisia, other studies showed the presence of T. ovis and B. ovis (M'ghirbi et al., ; Rjeibi et al., ), but none showed the presence of T. lestoquardi . Despite the low number of positive samples and the low geographic distribution area, further epidemiological studies are needed to conclude if T. lestoquardi is an emerging disease as it was reported during the last 10 years for the first time in three countries, namely Iraq, Oman and Iran.…”
Section: Discussionmentioning
confidence: 92%
“…The high prevalence rate determined in the current study compared to other regions may be attributed to differences in climatic conditions and sample collection times as observed by Yaghfoori [24]. Additionally, microscopic examination might not reflect the real prevalence rate of T. lestoquardi, as these piroplasms are difficult to be distinguished on morphological basis and need much expertise to differentiate between them [25]. A previous survey of T. lestoquardi, in Sudan included Wad-Medani town (ALGezira State) using Reverse Line Blot documented a high occurrence of T. ovis [26], this may explain the high prevalence of piroplasms observed in our study.…”
Section: Discussionmentioning
confidence: 65%